2020
DOI: 10.1177/0146167220907475
|View full text |Cite
|
Sign up to set email alerts
|

Men’s Hostile Sexism and Biased Perceptions of Partners’ Support: Underestimating Dependability Rather Than Overestimating Challenges to Dominance

Abstract: Hostile sexism expresses derogation of women’s competence and emphasizes that women will exploit men’s relational dependence. Men who endorse hostile sexism perceive their female partners more negatively, but do these negative perceptions stem from motives for dominance or insecurities about dependence? We tested both perspectives by assessing bias in perceptions of partners’ behaviors that challenge dominance (criticism, instruction, taking over) versus affirm partners are dependable (love, care, availability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Two of our recent papers demonstrate that insecurity about partners' dependability (rather than dominance) is pivotal in understanding the effects of men's hostile sexism in relationships. Hammond and Overall () found that men's hostile sexism predicted perceiving partners as being less dependable (e.g., loving and caring) than was warranted based on their partners' reports, and these negative biases arose particularly at times when partners were actually being less dependable. Moreover, this vigilant pattern of bias did not emerge for perceptions of partners' dominance (e.g., being critical and taking over).…”
Section: The Insecurity Within Men's Hostile Sexismmentioning
confidence: 99%
“…Two of our recent papers demonstrate that insecurity about partners' dependability (rather than dominance) is pivotal in understanding the effects of men's hostile sexism in relationships. Hammond and Overall () found that men's hostile sexism predicted perceiving partners as being less dependable (e.g., loving and caring) than was warranted based on their partners' reports, and these negative biases arose particularly at times when partners were actually being less dependable. Moreover, this vigilant pattern of bias did not emerge for perceptions of partners' dominance (e.g., being critical and taking over).…”
Section: The Insecurity Within Men's Hostile Sexismmentioning
confidence: 99%
“…Consistent with research revealing that the endorsement of benevolent sexism is significantly associated with higher levels of happiness, well-being, and life satisfaction among both men and women (e.g., Connelly & Heesacker, 2012; Hammond & Sibley, 2011; Napier et al, 2010), we hypothesized that both men and women’s relationship adjustment would be impacted positively by their own level of endorsement of benevolent sexism. In contrast, considering previous results indicating that men who endorse higher levels of hostile sexism tend to behave more negatively toward their partners and to be less satisfied with their relationship (e.g., Hammond & Overall, 2013, 2020), we postulated that men’s endorsement of hostile sexism would be negatively associated to their own and their partner’s relationship adjustment. Finally, considering that less is known about the consequences of women’s endorsement of hostile sexism toward their own gender, the examination of the links between this variable and both partners’ relationship adjustment is exploratory.…”
Section: Current Studymentioning
confidence: 78%
“…Their propensity for aggression is heightened when they feel manipulated or controlled by their partners (Cross et al, 2017). Researchers have documented that men who strongly endorse hostile sexism tend to maintain biased perceptions of their partners, perceiving their behavior as more critical, manipulative, and less supportive and dependable than appears merited based on their partners’ reports of that behavior (Hammond & Overall, 2013, 2020). These biased perceptions would involve insecurities about dependence and lead men to behave more negatively toward their partners and, in turn, to experience lower relationship satisfaction (Hammond & Overall, 2013, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mistrust of women associated with men’s hostile sexism has deleterious effects on intimate relationships. For instance, men who endorse hostile sexism perceive their partners as less committed (Cross et al, 2019) and less caring (Hammond & Overall, 2020) than is justified by their partner’s reports. In turn, these men tend to report lower relationship satisfaction (Cross et al, 2019; Hammond & Overall, 2013; Leaper et al, 2020), greater fear of intimacy (Fisher & Hammond, 2019; Yakushko, 2005), and more serious relationship problems (Cross & Overall, 2019; Leaper et al, 2020).…”
Section: The Harm Of Hostile Sexism For Women and For Intimate Relati...mentioning
confidence: 99%